2015
DOI: 10.1039/c5sc00473j
|View full text |Cite
|
Sign up to set email alerts
|

Using the gravitational energy of water to generate power by separation of charge at interfaces

Abstract: When water droplets (e.g., from rain) flow down a solid surface due to gravity, they can generate power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 22 publications
0
75
0
Order By: Relevance
“…With respect to applications, the motivation is to convert the kinetic energy of a flowing liquid directly to electrical energy. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] To this end, much literature has focused on how charging affects the dynamic wetting of surfaces, the movement of drops, and contact angle hysteresis. [17][18][19][20] However, the efficiency of charge separation by flowing liquids is still much lower than that of conventional electric generators.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to applications, the motivation is to convert the kinetic energy of a flowing liquid directly to electrical energy. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] To this end, much literature has focused on how charging affects the dynamic wetting of surfaces, the movement of drops, and contact angle hysteresis. [17][18][19][20] However, the efficiency of charge separation by flowing liquids is still much lower than that of conventional electric generators.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In these applications,t he liquid droplets are usually charged by ahigh-voltage power supply.Liquid can also be charged using other methods;examples include pressure-driven flows across initially uncharged channels (e.g., from millimeters to nanometers in size), [9][10][11][12] electrostatic induction (e.g., the Kelvin water dropper), and electrostatic charging of jumping droplets. [1][2][3][4][5][6][7][8] In these applications,t he liquid droplets are usually charged by ahigh-voltage power supply.Liquid can also be charged using other methods;examples include pressure-driven flows across initially uncharged channels (e.g., from millimeters to nanometers in size), [9][10][11][12] electrostatic induction (e.g., the Kelvin water dropper), and electrostatic charging of jumping droplets.…”
mentioning
confidence: 99%
“…ForP DMS, we found that the results are qualitatively similar to the case of nylon-the charge of the water droplet is approximately linearly proportional to the charge of PDMS (Figure 2b). [9,24] Hence,i ts eems that aw ater droplet can be charged either positively or negatively by ap iece of negatively charged PTFE, depending on the amount of negative charge the piece of PTFE has. Previous studies have shown that an uncharged solid surface can charge water droplets positively.…”
mentioning
confidence: 99%
See 2 more Smart Citations